2015
DOI: 10.1016/j.scitotenv.2015.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Thallium occurrence and partitioning in soils and sediments affected by mining activities in Madrid province (Spain)

Abstract: Thallium (Tl) and its compounds are toxic to biota even at low concentrations but little is known about Tl concentration and speciation in soils. An understanding of the source, mobility, and dispersion of Tl is necessary to evaluate the environmental impact of Tl pollution cases. In this paper, we examine the Tl source and dispersion in two areas affected by abandoned mine facilities whose residues remain dumped on-site affecting to soils and sediments of natural water courses near Madrid city (Spain). Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(25 citation statements)
references
References 37 publications
1
23
1
Order By: Relevance
“…Moreover, it seems thallium goes preferentially on illite clays instead of smectite (Voegelin et al, 2015) which is in accordance with the lower Tl affinity evidenced in this study. However, in many studies where sequential extractions are used, thallium associated to aluminosilicates is always assimilated to the residual fractions without exchange capacity (Vaněk et al, 2009(Vaněk et al, , 2013Gomez-Gonzalez et al, 2015). It is assumed that thallium is either in primary minerals such as micas or feldspar for instance (Vaněk et al, 2009;Gomez-Gonzalez et al, 2015) or substituted to K in illite interlayer space (Jacobson et al, 2005b;Vaněk et al, 2013;Voegelin et al, 2015).…”
Section: Implications For Thallium Mobility In the Environmentmentioning
confidence: 99%
“…Moreover, it seems thallium goes preferentially on illite clays instead of smectite (Voegelin et al, 2015) which is in accordance with the lower Tl affinity evidenced in this study. However, in many studies where sequential extractions are used, thallium associated to aluminosilicates is always assimilated to the residual fractions without exchange capacity (Vaněk et al, 2009(Vaněk et al, , 2013Gomez-Gonzalez et al, 2015). It is assumed that thallium is either in primary minerals such as micas or feldspar for instance (Vaněk et al, 2009;Gomez-Gonzalez et al, 2015) or substituted to K in illite interlayer space (Jacobson et al, 2005b;Vaněk et al, 2013;Voegelin et al, 2015).…”
Section: Implications For Thallium Mobility In the Environmentmentioning
confidence: 99%
“…The similarity of the metallic and covalent radii of Tl to that of lead (Pb) implies their similar behavioral patterns in the aquatic system (USEPA 1979). In freshwater, Tl can form complexes with inorganic and organic ligands through its oxidation of Tl(I) to Tl(III) by biological process (Scheckel et al 2004) and yet the ionic form of Tl(III) species can be the most abundant form in water resources (Gomez-Gonzalez et al 2015). However, with properties similar to that of potassium (K), Tl + can form even more stable compounds, while Tl 3+ can behave as a strong oxidant similar to aluminum (Al).…”
Section: Thallium Speciation In Agricultural Soilsmentioning
confidence: 99%
“…Other studies reported thallium concentrations in the order of 10 ppm in soils developing on sulphide-rich mineralization [16,17]. Anthropogenic sources of thallium are related to mining activities, either by the release of atmospheric thallium by smelters [18,19,20,21], or by developing on mining waste [22,23], with concentrations which might exceed 200 ppm. The permissible content in uncontaminated soils is 1 mg. kg [16,24].…”
Section: Introductionmentioning
confidence: 99%